To Block Lift or not to Block Lift? An Experiment at the Early Mesolithic Site of Star Carr, North-East Yorkshire, UK - P. Hadley; A. Hall; M. Taylor; A. Needham; B. Taylor; C. Conneller; N. Milner (Internet Archaeology, 2010)
As part of the excavations at Star Carr in the summer of 2007, a 'block' sample of peat from the archaeologically rich lake-edge deposits was removed for micro-excavation in the laboratory. The main aim was to compare on-site excavation and excavation in the laboratory. The techniques employed for the block were intended to maximise the chances of recovering fragile organic remains and provide an understanding of the spatial relationships between them. In addition, the time and resources required to excavate the block were evaluated in order to assess the merits of undertaking block lifting and excavation, with a view to informing future work.